The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00101-015-0071-1
|View full text |Cite
|
Sign up to set email alerts
|

S2e guideline: positioning and early mobilisation in prophylaxis or therapy of pulmonary disorders

Abstract: The German Society of Anesthesiology and Intensive Care Medicine (DGAI) commissioneda revision of the S2 guidelines on “positioning therapy for prophylaxis or therapy of pulmonary function disorders” from 2008. Because of the increasing clinical and scientificrelevance the guidelines were extended to include the issue of “early mobilization”and the following main topics are therefore included: use of positioning therapy and earlymobilization for prophylaxis and therapy of pulmonary function disorders, undesire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(61 citation statements)
references
References 314 publications
2
47
0
9
Order By: Relevance
“…Early mobilization therapy has been mentioned in order to prevent or attenuate physical function impairment in critically ill patients [ 11 ]. However, as studies showed an improved physical function associated to protocol-based early mobilization in a surgical ICU cohort [ 12 ], this could not be proven in patients with acute respiratory failure.…”
Section: Long-term Outcome After Acute Respiratory Distress Syndromementioning
confidence: 99%
“…Early mobilization therapy has been mentioned in order to prevent or attenuate physical function impairment in critically ill patients [ 11 ]. However, as studies showed an improved physical function associated to protocol-based early mobilization in a surgical ICU cohort [ 12 ], this could not be proven in patients with acute respiratory failure.…”
Section: Long-term Outcome After Acute Respiratory Distress Syndromementioning
confidence: 99%
“…In ECMO patients a specific strategy in terms of anticoagulation is mandatory [ 88 ]. Backrest elevated position (20–45°) is the preferred supine position for ARDS patients, since it may contribute to an improvement of oxygenation and respiratory mechanics [ 89 ] compared to “flat” supine, but limitations for backrest elevation (e.g., hemodynamic impairment) must be considered.…”
Section: Supportive Therapiesmentioning
confidence: 99%
“…This pilot study shows that such a protocol is feasible and safe in minimally-invasive cardiac surgery. Historically, so-called fast-track protocols in cardiac surgery were implemented 20 years ago during the evolution phase of the modern minimally invasive heart surgery [16][17][18]. These early protocols addressed primarily the intraoperative phase and showed the potential for an early extubation on the ICU, shortening of the ICU stay and cost containment in the cardiac surgical setting.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to mobilize the patient is made in consensus with the responsible anaesthetist. During this monitor-guided mobilization, we followed the break-off /stop criteria according to the recommendations of S2 guideline of the German Society of Anaesthesiology and Intensive Care Medicine [17]. First, the physiotherapist checks motoric and sensory functions of upper and lower extremities in supine position as well as the postoperative pain level.…”
Section: Postoperative Early Recovery Protocolmentioning
confidence: 99%